Technology spillover and absorptive capacity of firms and countries - Shujiro Urata; Youngmin Baek (Asian Development Bank Institute (ADBI), 2022)
The paper examines the foreign direct investment (FDI) spillover effects in developing countries and investigates the importance of the absorptive capacity of a firm and a country in realizing and facilitating FDI spillover. It uses data obtained from the World Bank's Enterprise Surveys for 107 countries from 2007 to 2020. The study finds that firms in developing countries do not benefit from horizontal FDI but benefit from forward and backward vertical FDI. The study also finds that firms can benefit from horizontal, forward, and backward FDI by improving the absorptive capacity of firms and host countries. Based on these findings, several recommendations are presented to help firms benefit from FDI spillover.
Keywords: D22; F21; O3; R1; 330; foreign direct investment; technology transfer; absorptive capacity